Inclusive Education Services for Children with Mild Intellectual Disabilities in Pandemic Period: The Dilemma of General Elementary Schools in Indonesia - Asep Supena; Uswatun Hasanah; Ahmad Januar (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2020)
Children with mild intellectual disabilities need to receive optimal educational services during the COVID-19 pandemic. This study aims to analyze inclusive education services for children with mild intellectual disabilities during the pandemic. This study used a survey method with a sample of 10 inclusive elementary schools in Jakarta with 25 teachers and 10 parents who have children with mild intellectual disabilities. The finding shows that inclusive education services in the sub-district of Setiabudi, South Jakarta need improvement and improvement in all aspects, from teachers, curriculum, media and in terms of parents. All components must contribute to providing optimal learning services for children with mild intellectual disabilities to match the vision of inclusive education itself, where schools make adjustments both in terms of curriculum, educational facilities and infrastructure, as well as learning systems tailored to the individual needs of students. Thus the results of this study can be used as benchmarks for us as academics, especially for policy makers to contribute to improving the quality of education, especially inclusive education services for children with special needs.